2021
DOI: 10.1051/0004-6361/202140346
|View full text |Cite
|
Sign up to set email alerts
|

Star-disk interaction in the T Tauri star V2129 Ophiuchi: An evolving accretion-ejection structure

Abstract: Context. Classical T Tauri stars are young low-mass systems still accreting material from their disks. These systems are dynamic on timescales of hours to years. The observed variability can help us infer the physical processes that occur in the circumstellar environment. Aims. In this work, we aim at understanding the dynamics of the magnetic interaction between the star and the inner accretion disk in young stellar objects. We present the case of the young stellar system V2129 Oph, which is a well-known T Ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 93 publications
2
8
0
Order By: Relevance
“…We also show the averaged veiling obtained for each target in Table 2. The veiling values increase from the Y to the K band for most of the targets, similar to the results found in previous works (e.g., Mc-Clure et al 2013;Sousa et al 2021;Alcalá et al 2021). Besides this general result, the average veiling for some individual targets remains the same from the Y to K band.…”
Section: Resultssupporting
confidence: 90%
“…We also show the averaged veiling obtained for each target in Table 2. The veiling values increase from the Y to the K band for most of the targets, similar to the results found in previous works (e.g., Mc-Clure et al 2013;Sousa et al 2021;Alcalá et al 2021). Besides this general result, the average veiling for some individual targets remains the same from the Y to K band.…”
Section: Resultssupporting
confidence: 90%
“…In order to further investigate the putative modulation at 8.33 d unveiled from the chromospheric indices, we compute the bidimensional periodogram of each emission line to quantify the evolution of the flux variability across the line profile, as it is commonly done for young PMS stars (e.g., Johns & Basri 1995;Bouvier et al 2007;Sousa et al 2021;Finociety et al 2021). We first normalize the continuum of each chromospheric line from the blaze-subtracted HARPS spectra in the stellar rest frame.…”
Section: Bidimensional Periodogram Analysismentioning
confidence: 99%
“…(2021) compared their results with the periodograms for the same system as was analyzed by Alencar et al (2012), and they found some differences on timescales of a decade, similarly to our results. Sousa et al (2021) discussed a few possible explanations for the observed phenomena, such as variations in the magnetic field strength, which would result in variations in the magnetospheric truncation radius, or latitudinal differential rotation, or a more complex magnetic structure with two major funnel flows originating at different radii in the inner disk. However, in the case of V2129 Oph, a periodicity longer than the stellar rotation period is present at the line center for a time of almost a decade.…”
Section: Line Morphology Variationsmentioning
confidence: 99%